2016
DOI: 10.11607/ijp.4358
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disinfectants on Antimicrobial and Physical Properties of Dental Impression Materials

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 0 publications
1
39
0
4
Order By: Relevance
“…In the current study Minuten was shown to be as effective as MD520 and ultrasound on both C. albicans and S. oralis spp. This is in contrast to previous research where it had a limited spectrum of activity and took longer for disinfection than other chemical disinfectants . Alcohol‐based disinfectants exhibited a good degree of effectiveness, with alginate being able to eradicate 99.27% and 100% of the microorganisms present …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study Minuten was shown to be as effective as MD520 and ultrasound on both C. albicans and S. oralis spp. This is in contrast to previous research where it had a limited spectrum of activity and took longer for disinfection than other chemical disinfectants . Alcohol‐based disinfectants exhibited a good degree of effectiveness, with alginate being able to eradicate 99.27% and 100% of the microorganisms present …”
Section: Discussionmentioning
confidence: 99%
“…Minuten and ultrasound for 15 seconds were not evaluated. Minuten was shown to be less effective than MD520 in a previous study, while the ultrasound applied for 15 seconds was not as effective as the longer application of ultrasound. Specimens without disinfection were used as controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Durante o procedimento de moldagem, o hidrocoloide irreversível entra em contato direto com a microbiota oral do paciente e, após reação de presa, agrega microrganismos presentes no meio bucal [1][2][3] em quantidade superior a outros materiais de moldagem, como silicones 4 . Dessa forma, é imprescindível a realização da desinfecção de moldes de hidrocoloide irreversível para evitar a transmissão de doenças infecciosas 5 .…”
Section: Introductionunclassified